Effect of Supervisor’s Role in Training Programs and Motivation to Learn As a Predictor of Job Performance - Azman Ismail; Larry M. Dooley; Sheela Chitra Chandra Segaran (Universitas Islam Indonesia, 2008)
Training research literature highlights that the ability of supervisors to play proper roles in training programs may directly increase job performance. More importantly, extant research in this field reveals that the effect of supervisor’s role in training programs on job performance is indirectly affected by motivation to learn. The nature of this relationship is less emphasized in training management literature. Therefore, this study was conducted to measure the effect of supervisor’s role in training programs and motivation to learn on job performance using 100 usable questionnaires gathered from technical employees who have worked in one city based local authority in Sarawak, Malaysia (MSCLAS). Outcomes of step-wise regression analysis showed that relationship between motivation to learn and supervisor role characteristics (i.e., support and communication) positively and significantly correlated with job performance. This result confirms that motivation to learn does act as a full mediat-ing role in the training model of the studied organization. Implications of this study to training management theory and practice, methodological and conceptual limitations, as well as future directions are discussed.Keywords: supervisor’s role in training programs, motivation to learn, job performance